SINERGITAS KINERJA GURU PAI, KEPALA SEKOLAH DAN ORANG TUA DALAM MEMBENTUK KARAKTER RELIGIUS SISWA - Dewi Rohmah; M Jamhuri; Achmad Yusuf (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
Religious character is very urgent to developed by reason of our nation's condition that indicates the complexitiy of youth problems in religious norm violations, such as using drugs, bullies, brawl, porn addiction, promiscuity, free sex, unwed pregnancy, no respect for teachers and parents. Consequently, establishing religious charahters on students is necessary as a way to evercome adolescent problems, which requires synergy from various parties. This study aims to analyze about synergy of performance on Islamic religious education teacher, principal and parents, religious activity programs in arraged by school and to analyze supporting and inhbiting factors in establishing religious characters on students in SMA Negeri 1 Purwosari. The author uses qualitative descriptive approach with data collection techniques through interview observation and documentation. Based on study result, it discovers: (1) Synergy of performance on Islamic religious education teacher, principal and parents have been going properly, (2) School programme as religious activities is running regularly, (3) Supporting and inhibiting factors in establishing religious characters on students consists of internal and external factors. The young generation as the successor of the nation is expected to able to advance the nation through intelligence and achievements. However, nowadays many of our young generation are slowly undermined by these addictive substance.